A Reappraisal of the Relationship Between Benjamin Britten and Walter Greatorex - Coyle, Jim (Current Musicology, 2020)
Walter Greatorex was Music Master at Gresham’s School from 1911 to 1936. Benjamin Britten was his pupil from 1928-1930 (aged 14-16). The received view is that Britten despised him as incompetent, unimaginative and reactionary. This view is based on Britten’s letters home from Gresham’s and an often repeated passage from Imogen Holst’s 1966 biography of Britten. This paper views these pieces of evidence in their wider context, and draws on new primary sources from Gresham’s School archives to question this opinion. It seeks to demonstrate that Greatorex was a musician and teacher of considerable gifts. Further, his commitment to including all members of the school community in music making might be seen as subliminally influential on Britten’s view of his own place in society and on his poly-technical works such as St Nicolas (1948), The Little Sweep (1949) and Noye’s Fludde (1958).